Development of a variable frequency artificial larynx and some behavioral studies - M, Jayaram (Journal of All India Institute of Speech and Hearing)
Voice, the vehicle of speech and language, is the result of the interaction of the air flow from the lungs and the vibration of the vocal cords. However, there are some people whose larynx has been surgically removed because of the carcinoma of the larynx or for some other reason. If it may be said that speech is our most important characteristic, then it follows that the surgical removal of the larynx affects the most human part of us.